Rational Choice Theory and Taste of Japanese Popular Culture in Motivation of PMI to Enter Japan's Global Labor Market - Shofy Yasmin; Kurniawaty Iskandar (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
Developed countries as the axis of world industrialization attract developing countries with young demographic conditions to participate in the global labor market. According to the ILO's World Employment and Social Outlook-Trends 2019, the participation of the youth workforce has decreased. Besides being faced with an aging population, Japan also has a shortage of workers in the middle and low-skilled sectors. Meanwhile, Indonesia has the potential to experience a demographic bonus. The TITP / Kenshusei scheme is a realization of the labor demand and supply relationship. Rational Choice Theory by Coleman focuses on the rational actions of individuals in making decisions to achieve goals, with the calculation of benefits. According to Sonja Haug, indicators of capital and cultural capital influence the decision-making of migrant workers to migrate. In Futaba, workers from developing countries in Japan describe a relationship of mutual need. The state rationally forms a labor mobility policy in the era of the global labor market. Futaba then found that most participants drive-by economic needs and limited employment opportunities in their home countries. Based on the three indicators, career orientation and financial adequacy are the main factors besides the popularity of Japanese culture. Institutionally, the role of the family is the motivation for migration to meet financial needs at the beginning of a career. There is a process of adopting a lifestyle to the way of interaction and cultural habits of Japanese society. Herewith Japanese popular culture such as; the film, anime, manga, and game industries have contributed to the motivation of migrant workers to Japan.